GLOBAL INTEGRATION AS FACTOR OF THE INTRODUCTION OF KAZAKHSTAN IN THE WTO: LEGAL PROBLEMS AND PROSPECTS - Aiymgul, Tleuzhanova; Elizaveta, Li (European Scientific Journal, ESJ, 2015)
The World Trade Organization (WTO) as the only international body which is engaged in global rules of trade between the states carries out such tasks as assistance in streamlining of process of trade within the system based on certain rules; objective settlement of trade disputes between the governments; organization of trade negotiations. 60 agreements of the WTO— the main precepts of law of policy of the international commerce and trade are the cornerstone of this activity. The principles on which these agreements are based, include lack of discrimination (the mode of the most favored nation and the provision on a national treatment), more free terms of trade, encouragement of the competition and additional provisions for the least developed countries. One of the purposes of the WTO is fight against protectionism. Since the creation activity of the WTO served as a forum for successful negotiations on opening of the markets in the field of telecommunications, information processing equipment and financial services. She participated in settlement more than 200 trade disputes and continues to watch implementation of the agreements adopted within the WTO. In article analyzed a role of the WTO in the course of integration of the states into world economic space, preconditions and prospects of accession to WTO in the conditions of globalization and legal preconditions, the basic positive and negative aspects of the introduction of Republic of Kazakhstan in the WTO.